The moral intelligence scale: Ukrainian language version adaptation - Myloslavska, Olena; Fursova, Kateryna (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2026)
This article presents the results of the adaptation of the Ukrainian-language version adaptation of the Moral Intelligence Scale (F. Alsmeheen). Moral intelligence is defined as an individual’s ability to apply universal ethical principles to their own value system, life goals, and behavioral actions. The development of moral intelligence is significantly influenced by a person’s emotional stability, conscientiousness, and openness. It was found that instrument original 6-factor structure was not confirmed in the Ukrainian sample, which may be due to the fact that, in our sociocultural and mental environment, internal moralities undergo significant pragmatization criteria. The adaptation process involved the removal of items with low significance and high uniqueness, which contributed to enhancing an instrument structural integrity. The Ukrainian-language version of the Moral Intelligence Scale includes three scales (“Prosocial Orientation,” “Intercultural Tolerance and Respect,” “Self-Regulation”) and a moral intelligence integrated measure. The Ukrainian-language version contains ten items, compared to thirty in the original. The indices of internal consistency and convergent validity questionnaire’s factors were found to be sufficient. The new model demonstrated excellent discriminant validity, as evidenced by the low level of latent intercorrelations among the subscales. Overall structure’s indicators fit with the empirical data pointed to the questionnaire’s high structural validity, allowing the Moral Intelligence Scale to be considered a promising, reliable, and concise psychodiagnostic tool within the domestic research landscape.